2021
DOI: 10.1002/chem.202100096
|View full text |Cite
|
Sign up to set email alerts
|

Na2FePO4F/Biocarbon Nanocomposite Hollow Microspheres Derived from Biological Cell Template as High‐Performance Cathode Material for Sodium‐Ion Batteries

Abstract: We have successfully synthesized Na 2 FePO 4 F/biocarbon nanocomposite hollow microspheres from Fe III precursor as cathodes for sodium-ion batteries through selfassembly of yeast cell biotemplate and sol-gel technology. The carbon coating on the nanoparticle surface with a mesoporous structure enhances electron diffusion into Na 2 FePO 4 F crystal particles. The improved electrochemical performance of Na 2 FePO 4 F/biocarbon nanocomposites is attributed to the larger electrodeÀ electrolyte contact area and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…A detailed calculation of a single titration step can be seen in Figure S6. The results show that the sodium diffusion coefficients D Na + of the NFPF/C/rGO electrodes vary from 10 –8 to 10 –11 cm 2 s –1 , which is at the same level of Na 2 FePO 4 F materials synthesized by other methods, ,, further confirming the reliability of the synthesis approach. The high sodium diffusion coefficients also explain the high specific capacity, flat platforms, good rate performance, and fast-charging properties of NFPF/C/rGO.…”
Section: Results and Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A detailed calculation of a single titration step can be seen in Figure S6. The results show that the sodium diffusion coefficients D Na + of the NFPF/C/rGO electrodes vary from 10 –8 to 10 –11 cm 2 s –1 , which is at the same level of Na 2 FePO 4 F materials synthesized by other methods, ,, further confirming the reliability of the synthesis approach. The high sodium diffusion coefficients also explain the high specific capacity, flat platforms, good rate performance, and fast-charging properties of NFPF/C/rGO.…”
Section: Results and Discussionsupporting
confidence: 65%
“…Among them, Na 2 FePO 4 F stands out because of its rapid Na + intercalation/deintercalation, unique 2D layered crystal structure, flat voltage plateaus (2.9 and 3.1 V), high theoretical specific capacity (124 mA h g –1 ), and low volume change (around 3.7%). ,, These intriguing features aroused great interest among researchers to improve the electrochemical properties of Na 2 FePO 4 F, which, on the other hand, suffers from low electronic conductivity and sluggish reaction kinetics. Carbon-modified Na 2 FePO 4 F composites with various nanostructures, such as ultrasmall Na 2 FePO 4 F embedded in porous N-doped carbon nanofibers, Na 2 FePO 4 F/C nanotubes, Na 2 FePO 4 F/biocarbon hollow microspheres, Na 2 FePO 4 F/C microspheres, and so forth, have been constructed and shown enhanced kinetics of sodium storage. However, the methods employed to construct these advanced nanostructures generally involve electrospinning, spray-drying, and template or sol–gel process, which are tedious, thus making it difficult to realize low-cost mass production.…”
Section: Introductionmentioning
confidence: 99%
“…They also assembled full cells (Figure 10f) that displayed energy density of 135.8 Wh kg –1 and capacity retention of 84.5% after 200 cycles at 0.5 C. Na 2 FePO 4 F microspheres were recently synthesized by using yeast cell templates. [ 78 ] The hollow structure is beneficial to increase the contact area between electrolyte and electrode and offer more active sites. The carbon coating layer derived from yeast cells effectively improves the electronic conductivity of the material and controls the particle size growth of the nanoparticles.…”
Section: Mixed‐polyanionsmentioning
confidence: 99%
“…The mainstream strategy to improve electronic conductivity is carbon coating. Carbon source or carbon material including glucose, [74] sucrose, [75] citric acid, [76] ascorbic acid, [77] biomass carbon, [78] carbon black, [79] CNT, [80] and rGO [81] etc. have been used to be uniformly coated the surface to enhance the electrical conductivity of the material and maintain structural stability.…”
Section: Development Of Electrochemical Performancementioning
confidence: 99%
“…have been widely investigated to compensate the performances targeting advanced SIBs. [7] It is reported that orthorhombic Nb 2 O 5 , which exhibits large interplanar lattice spacing of 3.9 Å for (001) planes, is beneficial to endow rapid Na + insertion and accommodate volume expansion. [8] As such, incorporating Nb 2 O 5 into carbon Sodium-ion batteries (SIBs) have attracted much attention for their advantages of high operating voltage, environmental friendliness and cost-effectiveness.…”
mentioning
confidence: 99%